Tingkat Prokrastinasi Akademik Siswa Kelas XI SMA Negeri 11 Semarang - Muhammad Irham Fazlurrahman; Siti Fitriana; Andarini Bhakti Sativa (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2024)
This study aims to portray the academic procrastination behavior experienced by the 11th grade students of SMA N 11 Semarang. The results of the identification are expected to describe the level of academic procrastination of students in class XI SMA N 11 Semarang. This research was conducted using a descriptive quantitative type that will produce a complete description of the research results. This research approach aims to describe the level of academic procrastination of students, the population of the study is the XI grade students of SMA N 11 Semarang totaling 96 students. The sample collection technique in this study is simple random sampling technique.